Quantitative evaluation of contrast agent uptake in standard fat‐suppressed dynamic contrast‐enhanced MRI examinations of the breast. Issue 1 (30th November 2017) - Kousi, Evanthia; Smith, Joely; Ledger, Araminta E.; Scurr, Erica; Allen, Steven; Wilson, Robin M.; O'Flynn, Elizabeth; Pope, Romney J.E.; Leach, Martin O.; Schmidt, Maria A.
Abstract : Purpose: To propose a method to quantify T1 and contrast agent uptake in breast dynamic contrast‐enhanced (DCE) examinations undertaken with standard clinical fat‐suppressed MRI sequences and to demonstrate the proposed approach by comparing the enhancement characteristics of lobular and ductal carcinomas. Methods: A standard fat‐suppressed DCE of the breast was performed at 1.5 T (Siemens Aera), followed by the acquisition of a proton density (PD)‐weighted sequence, also fat suppressed. Both sequences were characterized with test objects (T1 ranging from 30 ms to 2, 400 ms) and calibration curves were obtained to enable T1 calculation. The reproducibility and accuracy of the calibration curves were also investigated. Healthy volunteers and patients were scanned with Ethics Committee approval. The effect of B0 field inhomogeneity was assessed in test objects and healthy volunteers. The T1 of breast tumors was calculated at different time points (pre‐, peak‐, and post‐contrast agent administration) for 20 patients, pre‐treatment (10 lobular and 10 ductal carcinomas) and the two cancer types were compared (Wilcoxon rank‐sum test). Results: The calibration curves proved to be highly reproducible (coefficient of variation under 10%). T1 measurements were affected by B0 field inhomogeneity, but frequency shifts below 50 Hz introduced only 3% change to fat‐suppressed T1 measurements of breast parenchyma in volunteers. The values of T1 measured pre‐, peak‐, and post‐contrast agent administration demonstrated that the dynamic range of the DCE sequence was correct, that is, image intensity is approximately directly proportional to 1/T1 for that range. Significant differences were identified in the width of the distributions of the post‐contrast T1 values between lobular and ductal carcinomas ( P < 0.05); lobular carcinomas demonstrated a wider range of post‐contrast T1 values, potentially related to their infiltrative growth pattern. Conclusions: This work has demonstrated the feasibility of fat‐suppressed T1 measurements as a tool for clinical studies. The proposed quantitative approach is practical, enabled the detection of differences between lobular and invasive ductal carcinomas, and further enables the optimization of DCE protocols by tailoring the dynamic range of the sequence to the values of T1 measured.